Scaling laws for unmitigated pile driving: Dependence of underwater noise on strike energy, pile diameter, ram weight, and water depth. (September 2022) - von Pein, Jonas; Lippert, Tristan; Lippert, Stephan; von Estorff, Otto
Highlights: Scaling laws for underwater noise of offshore pile driving. The influence of strike energy, pile diameter, ram weight, and water depth on the sound exposure level. Scaling offshore pile driving noise. Measurement data of offshore pile driving noise. Scaling measured underwater noise data from pile driving. Abstract: Sound produced by marine pile driving activities poses a possible risk to marine life. The assessment and mitigation of this risk requires a prediction of the expected sound levels. While different analytical models have been presented to estimate the decay characteristics of pile driving noise, the estimation of the source level still requires the use of numerical modelling in most cases. The paper at hand discusses the possibilities and limits of estimating approximate source or any other levels by scaling laws, using measurement data from previous projects. The identified main influencing factors include strike energy of the hammer, pile diameter, ram weight, and water depth. The scaling laws are derived from theoretical considerations verified against results of a state-of-the-art finite element model for pile driving noise radiation. The found dependencies are then validated against a set of offshore measurement results. It is shown that the obtained scaling laws provide an option to approximately estimate the sound exposure levels of pile driving activities from one site to the other, within practical ranges of accuracy.